Investigation of propylene carbonate synthesis regularities by the interaction of propylene glycol with carbamide - A. V. Sulimov; A. V. Ovcharova; G. M. Kravchenko; Yu. K. Sulimova (Тонкие химические технологии)
Objectives. Cyclic carbonates are important products of organic synthesis, which are widely used as solvents, catalysts, and reagents for the production of various compounds (in particular, urethane-containing polymers) by the non-isocyanate method. The process of carbamide alcoholysis with polybasic alcohols is a promising method for the synthesis of cyclic carbonates. The purpose of this study is to determine the reaction conditions for the interaction of propylene glycol with carbamide in the presence of zinc acetate as a catalyst.Methods. We conducted experiments to study the synthesis of propylene carbonate in a batch laboratory apparatus. Moreover, we analyzed the starting reagents and final products using gas–liquid chromatography.Results. We studied the synthesis of propylene carbonate by carbamide alcoholysis with propylene glycol in the presence of a catalyst (zinc acetate) by varying the following parameters: initial molar ratio of propylene glycol/carbamide = (0.5–5):1, synthesis temperature 130–190°С, reagent residence time in the reactor 0.5–4 h, and the catalyst amount in the reaction mixture 0–1.5 wt %.Conclusions. We determined the technological parameters of propylene carbonate synthesis in a batch reactor. Moreover, we showed that the process allowed the production of propylene carbonate with a sufficiently high yield of 80%—at the initial molar ratio of propylene glycol/ carbamide = 3:1, temperature 170°C, and residence time 2 h.